Implied Open‐circuit Voltage Imaging via a Single Bandpass Filter Method—Its First Application in Perovskite Solar Cells. (18th November 2022) - Soufiani, Arman Mahboubi; Lee‐Chin, Robert; Fassl, Paul; Mahmud, Md Arafat; Pollard, Michael E.; Zheng, Jianghui; Weber, Juergen W.; Ho‐Baillie, Anita; Trupke, Thorsten; Hameiri, Ziv
Abstract: A novel, camera‐based method for direct implied open‐circuit voltage (i V OC ) imaging via the use of a single bandpass filter (s‐BPF) is developed for large‐area photovoltaic solar cells and precursors. The photoluminescence (PL) emission is imaged using a narrow BPF with centre energy inside the high‐energy tail of the PL emission, utilising the close‐to‐unity and nearly constant absorptivity of typical photovoltaic devices in this energy range. As a result, the exact value of the sample's absorptivity within the BPF transmission band is not required. The use of an s‐BPF enables a fully contactless approach to calibrate the absolute PL photon flux for spectrally integrated detectors, including cameras. The method eliminates the need for knowledge of the imaging system spectral response. Through an appropriate choice of the BPF centre energy, a range of absorber compositions or a single absorber with different surface morphologies, such as planar and textured, can be imaged, all without the need for additional detection optics. The feasibility of this s‐BPF method is first validated. The relative error in i V OC is determined to be ≤1.5%. The method is then demonstrated on device stacks with two different perovskite compositions commonly used in single‐junction and monolithic tandem solar cells. Abstract : A direct implied‐ V OC imaging method via the novel use of a single bandpass filter (s‐BPF) is developed for large‐area photovoltaic solar cells and solar cell precursors with multiple advantages over the existing calibration methods for camera‐based spectrally‐integrated imaging tools. This method images the luminescence emission using a narrow BPF with centre energy in the high‐energy tail of the luminescence emission.